Respuesta :

Well, this is a good practice of indices.

All of the numbers involved have the same base.

so, for the inner bracket, the powers will be (division is a minus sign for the powers):
[tex]\frac{5}{4}+\frac{1}{4}-\frac{1}{2}=1[/tex]

So the inner value is
[tex](4^{1})^{\frac{1}{2}}=4^{\frac{1}{2}} = 2[/tex]

Answer:  2

Step-by-step explanation:

The given expression : [tex](\dfrac{4^{\frac{5}{4}}\cdot4^{\frac{1}{4}}}{4^{\frac{1}{2}}})^{\frac{1}{2}[/tex]

Using product rule of exponents :

[tex]a^m\cdot a^n= a^{m+n}[/tex]

we get

[tex](\dfrac{4^{\frac{5}{4}}\cdot4^{\frac{1}{4}}}{4^{\frac{1}{2}}})^{\frac{1}{2}}\\\\=(\dfrac{4^{\frac{5}{4}+\frac{1}{4}}}{4^{\frac{1}{2}}})^{\frac{1}{2}}\\\\=(\dfrac{4^{\frac{5+1}{4}}}{4^{\frac{1}{2}}})^{\frac{1}{2}}\\[/tex]

[tex]=(\dfrac{4^{\frac{3}{2}}}{4^{\frac{1}{2}}})^{\frac{1}{2}}[/tex]

Using division rule of exponents :

[tex]\dfrac{a^m}{a^n} =a^{m-n}[/tex]

[tex](\dfrac{4^{\frac{3}{2}}}{4^{\frac{1}{2}}})^{\frac{1}{2}}=(4^{\frac{3}{2}-\frac{1}{2}})^{\frac{1}{2}}\\\\=(4^{\frac{3-1}{2}})^{\frac{1}{2}}\\\\=(4^{\frac{2}{2}})^{\frac{1}{2}}\\\\=(4^1})^{\frac{1}{2}}=(2\times 2)^{\frac{1}{2}}= (2^2)^{\frac{1}{2}}=2[/tex]

Hence, the correct answer [tex](\dfrac{4^{\frac{5}{4}}\cdot4^{\frac{1}{4}}}{4^{\frac{1}{2}}})^{\frac{1}{2}= 2[/tex]